Impact of Warming on Greenhouse Gas Production and Microbial Diversity in Anoxic Peat From a Sphagnum-Dominated Bog (Grand Rapids, Minnesota, United States) - Kolton, Max; Marks, Ansley; Wilson, Rachel M.; Chanton, Jeffrey P.; Kostka, Joel E. (Frontiers in Microbiology, 2019)
Climate warming is predicted to increase heterotrophic metabolism in northern peatland soils leading to enhanced greenhouse gas emissions. However, the specific relationships between temperature and the greenhouse gas producing microbial communities are poorly understood. Thus, in this study, the temperature dependence of carbon dioxide (CO2) and methane (CH4) production rates along with abundance and composition of microbial communities were investigated in peat from a Sphagnum-dominated peatland, S1 bog (Minnesota, USA). Whereas CH4 production rates increased with temperature up to 30°C, CO2 production did not, resulting in a lower CO2:CH4 ratio with increasing temperature. CO2 production showed both psychrophilic and mesophilic maxima at 4°C and 20°C, respectively, and appears to be mediated by two anaerobic microbial communities, one that operates under psychrophilic conditions that predominate for much of the year, and another that is more active under warmer conditions during the growing season. In incubations at 10°C above the ambient range, members of the Clostridiaceae and hydrogenotrophic methanogens of the Methanobacteriaceae dominated. Moreover, a significant negative correlation between temperature and microbial diversity was observed. Results indicate that the potential consequences of warming surface peat in northern peatlands include a large stimulation in CH4 production and a significant loss of microbial diversity.